Samozdravljenje z zdravili naravnega izvora - Janeš, Damjan (Farmacevtski vestnik, 2011)
The use of herbal medicinal products increases constantly and there is growingevidence that herbal medicines are used widely by all groups of societyincluding children, pregnant and breastfeeding mothers, women during the menopause, and the elderly. Of particular importance is the use of herbal medicines by patients with a wide range of conditions many of whom take prescription medicines and are reluctant to tell their doctors about herbal medicinal products or even food supplements they are taking. Data on potentialadverse effects and herb-drug interactions increase every year and healthcare professionals need to be aware of this problem and need to understand its effects to be able to offer the patient an adequate advice. Herbal medicinal products can offer an alternative to conventional medicines in non-life-threatening conditions, providing they are of adequate quality, safety and efficacy, and are used in an appropriate manner
Keywords: medsebojno delovanje zdravil; neželeni učinki; samozdravljenje; zdravila rastlinskega izvora